Unravelling the oxygen influence in cubic bixbyite In2O3 on Raman active phonon modes by isotope studies - Feldl, Johannes; Gillen, Roland; Maultzsch, Janina; Papadogianni, Alexandra; Kler, Joe; Galazka, Zbigniew; Bierwagen, Oliver; Ramsteiner, Manfred (Journal of Materials Chemistry C, 2025)
In this study, we performed comprehensive investigations on the Raman active phonon modes in cubic bixbyite In2O3, an important oxide based, wide-bandgap semiconductor. Fundamental insights into the lattice dynamics are revealed by determining the atomistic contribution to all modes and their frequencies using density functional perturbation theory calculations. These simulations were performed for different compositions of 16O and 18O isotope ratios, including their pure states. An increasing red-shift of the mode frequencies with increasing 18O content for all modes, due to the increased atomic mass, is revealed. For the seven lowest energy modes, this relative shift is below 1%, whereas for the remaining 15 higher energetic modes, a shift of about 5.5% was identified. All modes have energy contributions of both indium and oxygen lattice sites, except for one, which corresponds to a pure oxygen vibrational state. Using Raman spectroscopy, those results can be verified experimentally with excellent agreement. The investigated samples consisted of a bulk single crystal with 16O isotopes and a MBE grown thin film as the 18O sample. Time-of-flight secondary ion mass spectrometry confirms the purity of the oxygen isotope in the sample. These isotopologue studies allow for a direct experimental access to fundamental material properties in cubic In2O3 by means of Raman spectroscopy. For example, we speculate that the presence of oxygen vacancies in In2O3 would result in a shift of modes that are dominated by O-vibrations, e.g., E(4)g or A(4)g, towards lower frequencies.
CRIS-Team Scopus Importer:2025-10-24